Tyrosine phosphorylation as evidence of epididymal cauda participation in the sperm maturation process of Corynorhinus mexicanus bat. (17th March 2015) - Rodríguez‐Tobón, Ahiezer; Fierro, Reyna; León‐Galván, Miguel Angel; Rosado, Adolfo; Cortés‐Barberena, Edith; Arenas‐Ríos, Edith
Abstract: The bat Corynorhinus mexicanus provides an interesting experimental model for the study of epididymal sperm maturation because after spermatogenesis and the regression of the testes, this bat stores sperm in the epididymal cauda for several months. Earlier research conducted by our group suggested that sperm maturation in this species must be completed in the caudal region of the epididymis. One of the major signal transduction events during sperm maturation is the tyrosine phosphorylation of sperm proteins. The aim of the present study was to comparatively evaluate tyrosine phosphorylation in spermatozoa obtained from the caput, corpus and cauda of the epididymis during the sperm storage period. The maturation status of the sperm was determined by the percentage of capacitation and tyrosine phosphorylation in sperm obtained from the epididymis. The highest proportion of tyrosine phosphorylation was registered after the sperm had reached the cauda epididymis during the middle of the storage period. In conclusion, in Corynorhinus mexicanus and most likely in other chiropteran species with an asynchronous male reproductive pattern, epididymal sperm maturation ends in the caudal region of the epididymis and is related to the time that the sperm remains in the epididymis before mating activity.